Synthesis of hupehenols A, B, and E from protopanaxadiol. Issue 42 (12th April 2016) - Shao, Li-Dong; Xu, Jun; Li, Xiao-Nian; Zhang, Zhi-Jun; Shi, Xin; Ren, Jian; He, Juan; Zhao, Yu; Leng, Ying; Xia, Chengfeng; Zhao, Qin-Shi
Abstract : A unified semisynthesis approach from protopanaxadiol to hupehenols A, B, and E was described. The synthesis provided the primary SAR and the possibility of further medicinal development of hupehenols. Abstract : Hupehenols A–E (3–7) are bioactive octanordammarane triterpenoids, among which hupehenols B (4) and E (7) are the most potent and selective human 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) inhibitors (IC50 = 15 and 34 nM, respectively). Herein, the hupehenols were synthesized from protopanaxadiol, the main component of Panax notoginseng . The different synthetic attempts resulted in the stereoselective synthesis of hupehenols A, B, and E for further biological exploration. Notable features of the synthesis included a regioselective epoxide-opening reaction, regioselective acetylation, and a late-stage stereoselective oxa-Michael addition. Semi-synthetic derivatization of these natural products led to the determination of their absolute configurations, a better understanding of their inherent reactivity patterns, and the required C-17 configuration for murine 11β-HSD1 inhibition. These studies provide the basis for the synthesis of 11β-HSD1 inhibitors as potential targets for the treatment of type 2 diabetes.